JORDANIAN TEACHERS' USE OF TAPES AND TAPE RECORDERS IN ENGLISH LESSONS OF THE LOW PRIMARY STAGE - Abdallah Hussein El-Om (European Scientific Journal, ESJ, 2014)
This study aims at investigating the use of listening equipment- tapes and tape recorders- by Jordanian teachers of English at the low primary stage of the three main teaching sectors in Jordan (government, private, and UNRWA- United Nations for Relief and Works Agency). Ninety-nine teachers of English in the city of Irbid, Jordan responded to the two-part questionnaire of the study. The first consisted of 6 Yes / No questions about the availability and functionality of the equipment. The second has 16 items with five frequency responses about using the equipment and procedures of presenting the listening lessons as indicated by the textbook. The two parts of the questionnaire involve three variables; qualifications, gender, and school type. Results related to the qualification variable show no significant differences in equipment availability and use. The other two variables reflect significant differences for the female teachers of English over the male, and for the UNRWA and private teachers over the government regarding both of equipment availability and use.